Survey of Attitudes Toward Rapid HIV Testing and Current HIV Testing Procedures Among Patients in Baltimore (USA) STD Clinic - Sekiguchi, Mayu (Trinity Student Medical Journal, 2002)
Objectives: A survey-interview of 126 patients at the STD clinic in Baltimore, Maryland, USA was conducted to determine the patients’ perception and feelings toward existing HIV proce- dures as compared to rapid HIV testing. Rapid HIV testing can be performed in less than fif- teen minutes, as opposed to the traditional time-consuming ELISA test that takes 3.5 to 4 hours. Methods: Study subjects were between 14 and 68 years of age and were all patients of the STD clinic. The questionnaire surveyed patients’ experiences with HIV counseling, rea- sons for getting tested, perceptions of HIV risk and feelings toward rapid HIV testing. Results: 33.3% of the patients had previously failed to return for HIV test results. A signifi- cant number of the patients cited inconvenience as the most significant factor in not retriev- ing test results. Most said that they would prefer rapid HIV testing. Sixty nine percent of the patients claimed that they never received any type of pre-test counselling. However, among the patients who received some type of counseling at the Baltimore STD clinic, 58.3% rated the session favourably as 5 out of 5. These results suggest that routine HIV counseling should be improved, and that it may be advantageous to introduce rapid HIV testing as an option for HIV testing in STD clinics.